Supremacy of shari’ah in the islamic finance industry: comparative observations from selected jurisdictions - Md Nor, Mohd Zakhiri (American Scientific Publishers, 2018)
Today, the Islamic finance industry has made an impactful presence in many jurisdictions all over the world. It attracts practitioners and customers alike from both Muslims and non-Muslims. In essense, it is common knowledge that the principle of Islamic law (Shari’ah) is the supreme source of reference in an industry such as Islamic finance. Shari’ah is the true essence that makes up the Islamic finance industry. This paper examines the real-world legal framework of selected jurisdictions of Malaysia, Saudi Arabia, Pakistan and Sudan on how the rule provides for the supremacy of Shari’ah. This study involved three main components of Islamic finance: the ruler in the state administration, the Shari’ah scholar of the fatwa issuance body and the judge within the judiciary. Engaging in library-based research of data sources, this paper adopts the socio-legal research approach in analyzing how the local laws provide for the supremacy of Shari’ah within the chosen selected jurisdictions. The research found that albeit it is advocated that Shari’ah is the supreme source of reference in Islamic finance matters, the legal rules do not always provide for such position in express terms. In fact, few jurisdictions expressly provided that the main source of reference would be the local laws, instead of the Shari’ah. Hopefully this paper would contribute to the improvement in the policy making process of the selected jurisdictions with regards to the supremacy of Shari’ah in the Islamic finance industry.